Joint Sales Promotions in India - Innovations Beckon - Chandrasekar, K. S.; Senthil, M. (Indian Journal of Marketing, 2007)
Sales promotion in India is often related to discounts, coupons, exchange schemes etc. Many a time a company does more than what is possible. In such cases, innovations in the promotional front come into being. One such possibility is Joint promotions. When any sales promotion scheme, either for trade or consumer is announced by more than one company and or more than one brand of the same company, it is referred to as joint sales promotion or horizontal co-operative sales promotion or cross promotion or umbrella sales promotion. Sales promotional arrangements between one or more retailers or manufacturers are known as promotional tie-ins. Tie ins are used to combine resources of the business to promote products from all businesses involved. Joint promotions are one of the oldest marketing tools that companies employ to push sales. In the US, approximately 580 different products were reported to have been featured in various multi brand co-operative sales promotions during 1978 and 1979. In India, 56 such announcements of joint sales promotion were identified during the nineties.